Skills of Metamemory According to Some Variables (Field Study for Sample of Tishreen University Students) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This study aimed at identifying the level of metamemory with its three domains (satisfaction about memory, ability or memory's mistakes, memory's strategies) amongst Tishreen University students in the light of the variables of: gender, university year, academic specialization, and academic achievement level. The sample of the study consisted of (1102) students: (514) males and (588) females, distributed over the four years, in the faculties of humanities and science. To achieve the aim of the study, an Arabic version of Troyer and Rich's metamemory scale (Abu Ghazal, 2007) was used, the researcher extracted the validity and reliability for the scale. The results of the study revealed that the sample of the study showed a high level of metamemory at the total score level, and at the level of each domain separately. The results also indicated that there were statistical significant differences in metamemory level particularly in the satisfaction about memory and memory's strategies domains due to the gender in the favor of females, and there were statistical significant differences in metamemory level in all domains due to the academic achievement in the favor of the high achievers. The results also revealed that there were no statistical significant differences in metamemory level due to the university year level, and academic specialization, while statistical significant differences have appeared in satisfaction about memory due to the academic specialization in the favor of humanities.